2016
DOI: 10.17576/gema-2016-1603-04
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Word Exposure Frequency on Incidental Learning of the Depth of Vocabulary Knowledge

Abstract: This study examined the rate at which depth of vocabulary knowledge was learned and retained from reading a 300-headword graded reader, The Star Zoo. A total of 30 tertiarylevel students who learn English as a foreign language (EFL) in China volunteered to take part in a reading program. Incidental learning and retention of the depth of vocabulary knowledge was measured, complementing previous research along this line. The depth of vocabulary knowledge was examined by using 36 test items within six bands of fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
1
6
0
1
Order By: Relevance
“…It is certainly in line with the research conducted by Teng who found that the number of times that Chinese EFL learners needed to encounter a word to recognize vocabulary knowledge was 14 times, and at least 18 times were needed for productive vocabulary knowledge (Teng, 2016). It means that the exposures can play an essential role for the students who want to learn and expand their vocabulary.…”
Section: Discussionsupporting
confidence: 83%
“…It is certainly in line with the research conducted by Teng who found that the number of times that Chinese EFL learners needed to encounter a word to recognize vocabulary knowledge was 14 times, and at least 18 times were needed for productive vocabulary knowledge (Teng, 2016). It means that the exposures can play an essential role for the students who want to learn and expand their vocabulary.…”
Section: Discussionsupporting
confidence: 83%
“…However, both groups seemed to lack the ability for meta-cognitive self-regulation; thus, resulting in them engaging mainly in incidental learning. Teng (2016) in her study on vocabulary learning through reading concludes that words that are learned from incidental learning are not retained. Not undermining the value of incidental learning, it could be argued that there is still a need for purposeful learning to take place.…”
Section: Discussionmentioning
confidence: 99%
“…The theory of incidental learning posits that language learners often "pick up" new words through reading, listening and conversational activities [Hulstijn and others, 2003]. Incidental vocabulary acquisition has a direct link with frequency of exposure -the higher the frequency of exposure to a word, the higher will be the probability of a child committing it to memory [Teng, 2016]. We use the SUBTLEXus database (74,286 word forms) as a source of word frequency counts of different words used in spoken English language [Brysbaert and New, 2009].…”
Section: Frequency-based Modelmentioning
confidence: 99%